FOOD SOURCES OF IRON AND VITAMIN C CONSUMED AMONG INFANTS IN PRIMARY HEALTHCARE - Luana Lemos Leão; Barbara Andrade Antunes; Carolina Amaral Oliveira; Maria Fernanda Santos Figueiredo Brito; Lucinéia de Pinho (Universidade Federal do Paraná, 2018)
Objective: to evaluate the consumption of food sources of iron and vitamin C among children from 0 to 24 months. Methods: This cross-sectional study was carried out with 357 children during the vaccination campaign in November 2014 in Montes Claros, Minas Gerais, Brazil. The consumption of food sources of iron and vitamin C was evaluated using a food frequency questionnaire. A simple descriptive analysis was performed. Results: Breastfeeding was verified in 140 (93%) children younger than 6 months. Regarding the supplementary feeding of iron source foods, the consumption of cooked/ground meat was frequent in 80 (38.2%) children and the consumption of offal was low or absent in 147 (70.6%). All the children moderately or frequently consumed beans. Frequent consumption of oranges was reported in 74 (35.5%) children. Conclusion: The consumption of food sources of iron and vitamin C by children in Primary Healthcare presented a low-frequency, with a risk for iron deficiency anemia.